Evaluation and Treatment of Patients With Acetabular Osteolysis After Total Hip Arthroplasty. Issue 6 (15th March 2019) - Sheth, Neil P.; Rozell, Joshua C.; Paprosky, Wayne G.
Abstract : As the demand for total hip arthroplasty (THA) continues to increase, the burden of revision THA is also expected to increase. Although the quality of polyethylene has improved markedly, osteolysis continues to be a risk for older designs and younger, active patients. Although progressive but typically asymptomatic in early stages, osteolysis can result in component failure and complicate revision surgery. Serial radiographs are paramount for monitoring progression. Although select cases may be treated with observation, surgery should be considered based on age, activity level, and projected life span. Well-fixed, noncemented modular acetabular components may be treated with curettage and bone grafting, as well as having to bear liner exchange with retention of the acetabular shell. However, in the setting of osteolysis, it is controversial whether bone grafting and component retention is superior to cup revision. This review explores the pathophysiology of osteolysis after THA and provides a comprehensive analysis of the evaluation and treatment of patients with osteolysis.